The Influence of Human Resources Development and Governance on the Quality of Public Services in Tellulimpoe District - Sirma; Edi jusriadi; M.Yusuf Rendra Anggoror Kr (Pustaka Digital Indonesia, 2025)
The aim of this study is to determine the influence of human resource development and administrative governance capabilities on the quality of public services provided by village officials in Tellulimpoe District, Sinjai Regency. High-quality public services are essential for meeting community needs effectively, and both human resource development and governance play crucial roles in achieving this goal. This study employs a quantitative research method, with a sample consisting of 53 village officials selected through purposive sampling. The data collection process was conducted using structured questionnaires, ensuring comprehensive responses from the participants. The collected data were then analyzed using multiple linear regression techniques with SPSS version 25 to determine the relationships between the variables. The findings of this study reveal that human resource development has a positive and significant impact on the quality of public services. This suggests that well-trained and skilled village officials are more capable of delivering efficient and effective services to the community. On the other hand, administrative governance capabilities were found to have a negative and insignificant effect on service quality. This indicates that governance-related factors alone may not be sufficient to enhance public service quality without corresponding improvements in human resource capacity. Overall, the study highlights the importance of investing in human resource development to improve public service quality. Future research could explore additional factors that influence service quality, such as leadership, organizational culture, and technological advancements, to provide a more comprehensive understanding of public service improvement strategies.